2014
DOI: 10.1038/ncomms6031
|View full text |Cite
|
Sign up to set email alerts
|

Retro-biosynthetic screening of a modular pathway design achieves selective route for microbial synthesis of 4-methyl-pentanol

Abstract: Increasingly complex metabolic pathways have been engineered by modifying natural pathways and establishing de novo pathways with enzymes from a variety of organisms. Here we apply retro-biosynthetic screening to a modular pathway design to identify a redox neutral, theoretically high yielding route to a branched C6 alcohol. Enzymes capable of converting natural E. coli metabolites into 4-methyl-pentanol (4MP) via coenzyme A (CoA)-dependent chemistry were taken from nine different organisms to form a ten-step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 72 publications
1
56
0
Order By: Relevance
“…Although microbial FFAs have been produced for decades, recent work has demonstrated the potential for obtaining advanced fuels or valuable chemicals as derivatives of FFAs (50)(51)(52)(53). Based on the broad substrate range and known activities of carboxylic acid reductases, their addition to these pathways can result in production of C 4 to C 18 aliphatic aldehydes (25,26). Microbial synthesis of other valuable aldehyde classes, such as terpenoid aldehydes, could potentially occur in E. coli using variations of previously engineered terpenoid pathways (54).…”
Section: Engineering Aldehyde Biosynthetic Reactions and Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Although microbial FFAs have been produced for decades, recent work has demonstrated the potential for obtaining advanced fuels or valuable chemicals as derivatives of FFAs (50)(51)(52)(53). Based on the broad substrate range and known activities of carboxylic acid reductases, their addition to these pathways can result in production of C 4 to C 18 aliphatic aldehydes (25,26). Microbial synthesis of other valuable aldehyde classes, such as terpenoid aldehydes, could potentially occur in E. coli using variations of previously engineered terpenoid pathways (54).…”
Section: Engineering Aldehyde Biosynthetic Reactions and Pathwaysmentioning
confidence: 99%
“…Later publications from Rosazza and colleagues demonstrated that Car Ni requires one-time activation by a phosphopantetheinyl transferase and that Car Ni has activity in vitro on a broader range of substrates that includes several citric acid cycle dicarboxylic acids (23,24). Motivated by the activity of Car Ni on diverse carboxylic acid substrates, we investigated its activity on straight-chain and branched-chain aliphatic acids ranging from C 2 to C 8 (25). A homolog of Car Ni from Mycobacterium marinum was also demonstrated to have activity on straight-chain aliphatic acids ranging from C 6 to C 18 (26).…”
Section: Engineering Aldehyde Biosynthetic Reactions and Pathwaysmentioning
confidence: 99%
“…[22,25] Withint he context of metabolic pathwayi ncorporation, scientists in the Prather group used the Duet systemf or the biosynthesis of (R)-and (S)-3-hydroxybutyrate, [26] butanol [27] and the non-natural alcohols pentanol [28] and 4-methyl-1-pentanol. [29] Thel ast compound is formed via at en-step de novo pathway with enzymest aken from nine different microorganisms.I n the cases of non-naturala lcohol production, enzymes are groupedi nm odules that allowed rational combination of different modules to elevate product titers.…”
Section: The Challenges Of Multiple Recombinant Protein Expressionmentioning
confidence: 99%
“…Batch, 48 h Overexpression of LeuABCD pathway; Rational enzyme mutagenesis on leuA and kivD [28] E. coli 4-Methyl-pentanol 192 mg L À1 Batch, 48 h Retrosynthetic design for creation of de novo pathways [29] E. coli n-Pentanol 109 mg L À1 Batch, 48 h Retrosynthetic design for creation of >de novo pathways [30] Isoprenoids…”
Section: G L à1mentioning
confidence: 99%
“…Such an approach substantially increased the relative purity of products in E. coli strains harboring de novo pathways designed for 4-methyl-pentanol and n-pentanol. [29,30] …”
Section: Extended Linear-and Branched-chain Alcoholsmentioning
confidence: 99%